Vpliv vršičkanja na pridelek kanabinoidov in morfološke značilnosti industrijske konoplje (Cannabis sativa L.) - Eržen, Marjeta (Hmeljarski bilten, 2025)
Various techniques are used to improve the yield and vigor of hemp plants. One such technique is topping, which promotes the growth of lateral branches and increases yield per plant. In this study, we used ten industrial hemp (Cannabis sativa L.) varieties to investigate the effect of topping on cannabinoid content, inflorescence mass, plant height, and stem mass. The experiment included five dioecious and five feminized varieties. The highest total CBD content was observed in topped plants of the variety Midwest (14.3% and 42.5 g/plant), the highest total CBG content in topped plants of Berry Blossom (8.3% and 41.3 g/plant), and the highest total THC content in Tiborszallasi (0.8% and 1.8 g/plant). Topped plants were generally shorter for 6 cm than non-topped plants. The tallest plants were non-topped Fibranova (357 cm), while the shortest were topped Midwest (152 cm). Feminized varieties were for 129 cm shorter than dioecious ones. The yield of dry inflorescences was, in most varieties, higher in topped plants (e.g., Enectaliana, 226,9 g). There was no significant difference in inflorescence yield between feminized and dioecious varieties. The ratio between dry inflorescence mass and dry stem mass showed that, in most cases, the mass of dry inflorescences exceeded that of dry stems. An exception was the variety Northwest, where stem mass was higher. This study confirmed that topping plays an important role in hemp morphology, although its effect can be highly dependent on the variety.
Keywords: cannabinoids; Cannabis sativa L.; hemp; kanabinoidi; konoplja; pridelek; topping; vršičkanje; yield